Determination of future prevention strategies in elite track and field: analysis of Daegu 2011 IAAF Championships injuries and illnesses surveillance. Issue 7 (20th April 2012) - Alonso, Juan-Manuel; Edouard, Pascal; Fischetto, Giuseppe; Adams, Bob; Depiesse, Frédéric; Mountjoy, Margo
Abstract : Objective: To determine the incidence and characteristics of newly incurred injuries and illnesses during international Athletics Championships, by improving the medical surveillance coverage, in order to determine future prevention strategies. Design: Prospective recording of newly occurred injuries and illnesses. Setting: 13th International Association of Athletics Federations World Championships in Athletics 2011 in Daegu, Korea. Participants: National team and Local Organising Committee physicians; and 1851 registered athletes. Main outcome measures: Incidence and characteristics of newly incurred injuries and illnesses. Results: 82% of athletes were covered by medical teams participating with a response rate of 94%. A total of 249 injuries were reported, representing an incidence of 134.5 injuries per 1000 registered athletes, and 119 (48%) resulted in time loss from sport. A total of 185 injuries affected the lower limb (74%). Hamstring strain was the main diagnosis and 67% resulted in absence from sport. Overuse (n=148; 59%) was the predominant cause. A total of 126 illnesses were reported, signifying an incidence of 68.1 per 1000 registered athletes. Upper respiratory tract infection was the most common reported diagnosis (18%), followed by exercise-induced dehydration (12%), and gastroenteritis/diarrhoea (10%). The highest incidences of injuries were found in combined events and middle and long-distance events, and of illness in race walking events. Conclusion: During elite Athletics World Championships, 135 injuries, 60 time-loss injuries and 68 illnesses per 1000 registered athletes were reported. Higher risks of injuries were found in combined events and long-distance runs. Preventive interventions should focus on overuse injuries and hamstring strains, decreasing the risk of transmission of infectious diseases, appropriate event scheduling and heat acclimatisation.